Chemical Composition and In vitro Antibacterial and Cytotoxic Effect of Nigella sativa L. Seed Extract - Cyuzuzo, Callixte; Arwati, Heny; Irene, Tuyishimire; Shoukat, Shahzad (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Nigella sativa L. is a plant with high medicinal profile in the treatment of diseases. This study aimed to assess the chemical composition and in vitro antibacterial and cytotoxic effect of Nigella sativa L. seed extract. Seeds were purchased from supermarket and blended into powder using electric blender. The powder was macerated with 96% methanol. The extracts were then qualitatively screened to test the presence of secondary metabolites and agar well diffusion method was employed to study the antibacterial activity of extracts. In this evaluation, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used to examine the cytotoxic effect of extract on peripheral blood mononuclear cells (PBMCs). MTT assay was done on different extract concentrations for 3 days and the results were recorded daily. The findings revealed the presence of tannins, terpenoids, steroids, saponins, alkaloids, phenolic compounds and flavonoids. The antibacterial activity was observed with the inhibition zones ranging from 11.3 ±1.1 to 16.3 ±1.5mm while the minimum inhibitory concentration (MIC) values of extract ranged between 0.5 and 1.25 μg/mL. The black seed extracts contain bioactive substances with germicidal activity and in vitro administration of black seed extract up to the dose of 100 μg/mL resulted no cytotoxic effect on PBMCs.